2019
DOI: 10.1109/access.2019.2897922
|View full text |Cite
|
Sign up to set email alerts
|

Analogue Radio Over Fiber Aided MIMO Design for the Learning Assisted Adaptive C-RAN Downlink

Abstract: The cloud/centralized radio access network (C-RAN) architecture is recognized as a strong candidate for the next generation wireless standards, potentially reducing the total cost of ownership. Spatial modulation (SM) is a cost-effective multiple-input-multiple-output (MIMO) solution, where only a single-radio frequency chain is required for transmission. In this context, we propose analogue radio over fiber (A-RoF) aided MIMO techniques for learning assisted adaptive C-RAN system, where SM combined with space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The QoS degradation of A-RoF compared to the digital solution is not presented in this paper since we focused on the beamforming design using the proposed A-RoF system. However, this issue has been widely investigated and demonstrated in our recent papers[16],[19],[35] as well as other literatures[36],[37], where it is shown that A-RoF based system is capable of supporting 5G signals with an acceptable degradation of QoS. For example in[16], we experimentally verified that the A-RoF system is capable of supporting a 2 × 2 MIMO system with less than 1 dB SNR degradation compared to the traditional system…”
mentioning
confidence: 53%
“…The QoS degradation of A-RoF compared to the digital solution is not presented in this paper since we focused on the beamforming design using the proposed A-RoF system. However, this issue has been widely investigated and demonstrated in our recent papers[16],[19],[35] as well as other literatures[36],[37], where it is shown that A-RoF based system is capable of supporting 5G signals with an acceptable degradation of QoS. For example in[16], we experimentally verified that the A-RoF system is capable of supporting a 2 × 2 MIMO system with less than 1 dB SNR degradation compared to the traditional system…”
mentioning
confidence: 53%
“…To manage the rapidly increasing data rates, implementation costs will become a major challenge with D-RoF [14]. From this perspective, particularly, A-RoF-based C-RAN has attracted much attention in recent years [15], [16]. The analog-millimeter-wave-over-fiber fronthaul architecture [17] and the machine learning-based A-RoF C-RAN architecture [18] have also been discussed towards 6G communications.…”
Section: B C-ranmentioning
confidence: 99%
“…From this perspective, particularly, A-RoF-based C-RAN has attracted much attention in recent years [15], [16]. The analog-millimeter-wave-over-fiber fronthaul architecture [17] and the machine learning-based A-RoF C-RAN architecture [18] have also been discussed towards 6G communications. In these methods, the C-RAN is constructed by aggregating mobile signals using WDM.…”
Section: B C-ranmentioning
confidence: 99%
“…RoF is a suitable technology to cope with the on growing demand of high bandwidth multivariate wireless services both for outdoor and indoor scenarios [5][6][7], and is looked upon as an enabling technology for next generation networks [8], [9]. Moreover, thanks to the low attenuation of the optical fiber, the radio signals can be transmitted with a reduced need of repeaters or amplifiers.…”
Section: Introductionmentioning
confidence: 99%